Views of smoke in England, 1800-1830 - Kasuga, Ayuka (2013)
This thesis explores urban smoke and its nuisances in Georgian England, especially focusing on the period, 1800-1830. During this period, a number of English towns experienced accelerated industrialisation and many of them first experienced air pollution. In 1821, Michael Angelo Taylor, MP, passed a parliamentary bill on smoke abatement, Taylor’s Act. Although it has generally been believed that the Act did not have much of a social impact, this thesis argues that the Act diffused the usage of smoke abatement technology and triggered dozens of legal cases. The geographical focus of this thesis is Leeds and London. The Leeds case study examines the Leeds smoke abatement campaign and the smoke nuisance court case against Benjamin Gott, a leading merchant/ manufacturer in Leeds. It shows that the confusion over the effectiveness of smoke abatement technology represented the main difficulty in the smoke abatement campaign. The court case between the Duke of Northumberland and Clowes represents an example of the London nuisance cases in the 1820s. After the introduction of the steam press, the printing business became a polluting business. Because the plaintiff was the aristocrat, the case was interpreted as a class issue between aristocrat and middle-class printer. However, it was the Duke’s servants who suffered most from the nuisance and the case shows more complex class politics. This thesis also explores smoke nuisance caused by conventional smoke-producing industries in London, waterworks and brickmaking. Some water companies adopted smoke abatement technology but the confusion over the effectiveness of the technology can be observed in London, too. Taylor’s Act did not directly influence brickmaking business but it could cause nuisance to its neighbours, especially nurseries and gardens.